Impact of Positive Reinforcement Strategies on Classroom Behavior Management Using ABA (Journal of Advances and Scholarly Researches in Allied Education, 2026)
Parents and guardians have a responsibility to ensure that their children get the best care possible while they are in the care of early childhood educators.  Simultaneously, teachers' mental health and stress levels are affected since a third of the children in early childhood education programs come in with disruptive behaviours.  The purpose of the research was to find out how the instructors' use of reinforcement techniques affected their students' grades.  Students' self-esteem and ability to focus in class are both boosted by positive reinforcement.  Teachers' attention is mostly focused on individual pupils, but the effect on poor performers and benchwarmers is substantial.